PENGARUH CITRA DESTINASI DAN STRATEGI POSITIONING TERHADAP KEPUTUSAN BERKUNJUNG PADA DESTINASI WISATA PANTAI GEMAH KABUPATEN TULUNGAGUNG - Fahmi Alif Aldianto; Agus Eko Sujianto; Mashudi Mashudi (Institut Teknologi dan Bisnis Dewantara, 2023)
The problem raised from this study is regarding the influence of positioning strategy and destination image on tourists' visiting decisions to tourist destinations Gemah Beach, Tulungagung Regency. The research method used is quantitative, data analysis uses quantitative descriptions with multiple linear regression, while hypothesis testing uses determination tests, partial tests, and simultaneous tests as well as data processing with the help of the SPSS program with a sample consisting of 56 (fifty six) visitors using sampling cumulative. Data analysis used multiple regression tests and data processing using SPSS. The positioning strategy and destination image influence the decision to visit after conducting research. From this study, the following conclusions were drawn: tourists' decisions to visit the Gemah Beach tourist destination are positively and significantly influenced by the destination image and positioning strategy, while at the same time, destination image and positioning strategy have a positive and significant effect on the decision to visit a tourist destination Gemah Beach, Tulungagung Regency.